2021
DOI: 10.1186/s12935-021-02060-1
|View full text |Cite
|
Sign up to set email alerts
|

JOSD1 promotes proliferation and chemoresistance of head and neck squamous cell carcinoma under the epigenetic regulation of BRD4

Abstract: Background Deubiquitinating enzymes (DUBs) play critical roles in various cancers by modulating functional proteins post-translationally. Previous studies have demonstrated that DUB Josephin Domain Containing 1 (JOSD1) is implicated in tumor progression, however, the role and mechanism of JOSD1 in head and neck squamous cell carcinoma (HNSCC) remain to be explored. In this study, we aimed to identify the clinical significance and function of JOSD1 in HNSCC. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…ATXN3L directly interacted with KLF5, thus, reducing KLF5's ubiquitination and degradation (Ge et al, 2015). JOSD1 was found to be up-regulated in the head and neck squamous cell carcinoma (HNSCC) (Jing et al, 2021), gynaecological cancer (GC) cells (Wu et al, 2020), and acute myeloid leukemia (AML) cells (Yang et al, 2022). Overexpressed JOSD2 was positively correlated with the worse prognosis in hepatocellular carcinoma (Huang et al, 2022), cholangiocarcinoma (CCA) (Qian et al, 2021), and NSCLC (Krassikova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ATXN3L directly interacted with KLF5, thus, reducing KLF5's ubiquitination and degradation (Ge et al, 2015). JOSD1 was found to be up-regulated in the head and neck squamous cell carcinoma (HNSCC) (Jing et al, 2021), gynaecological cancer (GC) cells (Wu et al, 2020), and acute myeloid leukemia (AML) cells (Yang et al, 2022). Overexpressed JOSD2 was positively correlated with the worse prognosis in hepatocellular carcinoma (Huang et al, 2022), cholangiocarcinoma (CCA) (Qian et al, 2021), and NSCLC (Krassikova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, JOSD1 depletion reduced cell proliferation and colony formation, and promoted cisplatin‐induced apoptosis of HNSCC cells in vitro. Additionally, JOSD1 suppression inhibited the tumor growth and improved chemosensitivity against cisplatin in a xenograft mouse model 63 …”
Section: Ataxin‐3 (Atxn3)mentioning
confidence: 97%
“…Additionally, JOSD1 suppression inhibited the tumor growth and improved chemosensitivity against cisplatin in a xenograft mouse model. 63 Together, these aspects defined above may also be relevant for HCC or hepatocellular functions in general, but direct proof is currently missing.…”
Section: Cylindromatosis (Cyld)mentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation into the role of BRD4 in skin SCCs showed that it is required for the expression of cyclin D1, BCL-2 and MYC oncogenes (14). Similar studies have also shown that BRD4 collaborates with YAP1 (15) or JOSD1 (16) to promote the tumorigenesis of head and neck squamous cell carcinoma (HNSCC). Therefore, BRD4 is broadly recognized as an important therapeutic target in SCC; the fact that over 30 targeted inhibitors of various BET family members including BRD4 are currently in preclinical and clinical trials is testament to its perceived importance.…”
mentioning
confidence: 92%